SC Ibalizumab Warrants Further Study for Preventing HIV-1 Infection - Lederman, Lynne (MD Conference Express, 2014)
Among the strategies being explored to prevent infection with human immunodeficiency virus type 1 is ibalizumab, a humanized monoclonal antibody that binds to CD4 domain 2 and blocks the entry of HIV-1 into CD4-positive T cells. This article discusses the Safety Study of Ibalizumab Subcutaneous Injection in Healthy Volunteers (TMB-108) [NCT01292174] results of a study of the safety, tolerability, pharmacokinetics, and pharmacodynamics of subcutaneous injections of ibalizumab.